The anarchist tension - Bonanno, Alfredo M., 1937-2023 (London : Elephant editions, 1998)
Anarchism is not a concept that can be locked up in a word like a gravestone. It is not a political theory. It is a way of conceiving life, and life, young or old as we may be, whether we are old people or children, is not something definitive: it is a stake we must play day after day. When we wake up in the morning and put our feet on the ground we must have a good reason for getting up, if we don't it makes no difference whether we are anarchists or not. We might as well stay in bed and sleep